Gender difference in domain-specific quality of life measured by modified WHOQoL-BREF questionnaire and their associated factors among older adults in a rural district in Bangladesh. - Fakir M Amirul Islam (PLoS ONE)
Background The global population of older adults has steadily increased in recent decades. Little is known about the gender difference in the quality of life (QoL) of older adults in the general population. This study aimed to identify factors associated with QoL among older adults by gender. Method Data on QoL using the World Health Organization Quality of Life (WHOQoL-BREF) questionnaire and socio-demographic characteristics, including living status and sources of income, were collected from 1147 older adults. The WHOQoL-BREF has four domains: physical, psychological, social and environmental. Rasch analysis was used to compute a combined score from Likert-type data to a continuous scale ranging from 0% satisfaction to 100% satisfaction in terms of QoL for each domain. We used a generalized linear model to compare the mean rate of QoL for different factors, and logistic regression analysis was used to quantify the associations of factors with below-average QoL measured as 50% or less in QoL. Results The domain-specific QoL mean (standard error), minimum-maximum values were physical 48.9 (0.41), 7-86, psychological 38.9 (0.51), 4-71, social 50.5 (0.49), 8-92, and environmental domains 47.8 (0.37), 6-91 in the total sample with significant gender difference in all but social domain. The proportion of below average QoL for females vs. males was physical 47.6% vs. 42.6%, psychological 74.4% vs.66.7%; social 34.8% vs. 30.1% and environmental domains 56.1% vs. 49.0%. In females, participants living alone were associated with a higher proportion of below average QoL in physical OR 30.2, 95% CI 2.47, 370, psychological OR 9.54, 95% CI1.09,83.27 and social domains OR 5.94, 95% CI 1.25,28.34. In males, participants' sources of income from relatives were associated with a higher proportion of below average QoL in physical OR 3.6, 95% CI 2.01,6.44, psychological 30.2, 95% CI 2.47, 370, psychological OR 4.63 95% CI 2.56, 8.38, social domains OR 1.81, 95% CI 1.04, 3.16 and environmental domains OR 2.53 95% CI 1.44, 4.43 than those who had own income. Females engaged in income generation activities had better QoL in social and environmental domains than those with house duties, irrespective of their education or socioeconomic status. Males in retired life had the highest QoL in the social and environmental domains if they had better SES. Conclusions The study's findings reveal that more than 50% of people had below-average QoL in each domain, which is significant. The study also highlighted that females living alone and males without their own income had the poorest QoL. On a positive note, it was found that females engaged in any income generation activities had better QoL in social and environmental domains. These results provide valuable insights for policymakers and healthcare professionals. They underscore the importance of implementing appropriate intervention programs to enhance the QoL of older adults, reiterating the urgency and necessity of their work to improve the health and well-being of older adults.